Localization of an Ascorbate-Reducible Cytochrome b561 in the Plant Tonoplast - Griesen, Daniel (The American Society for Plant Biologists, 2004)
As a free radical scavenger, and cofactor, ascorbate (ASC) is a key player in the regulation of cellular redox processes. It is involved in responses to biotic and abiotic stresses and in the control of enzyme activities and metabolic reactions. Cytochromes (Cyts) b561 catalyze ASC-driven trans-membrane electron transport and contribute to ASC-mediated redox reactions in subcellular compartments. Putative Cyts b561 have been identified in Arabidopsis (ecotype Columbia) on the basis of sequence similarity to their mammalian counterparts. However, little is known about the function or subcellular localization of this unique class of membrane proteins. We have expressed one of the putative Arabidopsis Cyt b561 genes (CYBASC1) in yeast and we demonstrate that this protein encodes an ASC-reducible b-type Cyt with absorbance characteristics similar to that of other members of this family. Several lines of independent evidence demonstrate that CYBASC1 is localized at the plant tonoplast (TO). Isoform-specific antibodies against CYBASC1 indicate that this protein cosediments with the TO marker on sucrose gradients. Moreover, CYBASC1 is strongly enriched in TO-enriched membrane fractions, and TO fractions contain an ASC-reducible b-type Cyt with α-band absorbance maximum near 561 nm. The TO ASC-reducible Cyt has a high specific activity, suggesting that it is a major constituent of this membrane. These results provide evidence for the presence of trans-membrane redox components in this membrane type, and they suggest the coupling of cytoplasmic and vacuolar metabolic reactions through ASC-mediated redox activity.